Enhancing Innovative Thinking through a Theory-Based Instructional Model in Design Education to Support Sustainable Development Goals (SDGs) - Rui Di; Tatsirin Sawangboon; Jiraporn Chano (ASEAN Journal of Educational Research and Technology, 2025)
This study aimed to develop an instructional model that enhances innovative thinking skills in interior design students by integrating emotional design theory, constructivist learning theory, and creative thinking theory. Using a research and development approach, the model was constructed through needs analysis, expert validation, and empirical implementation. Pre-test and post-test comparisons, along with classroom observations and student feedback, demonstrated significant improvement in flexibility, fluency, originality, and precision of thinking. The model was particularly effective because it aligns theoretical learning with practical application, encouraging student engagement and deeper cognitive processing. As a result, students demonstrated increased creativity, improved design output, and greater collaborative capacity. The instructional model presents a promising framework for fostering innovation in design education. This study supports current issues in Sustainable Development Goals (SDGs).